AN ASSESSMENT OF FACTORS AFFECTING THE PROFITABILITY OF FIRMS IN CASE OF CHIRO TOWN TRADERS - Ismael Hussein Malela; Abdela Ahmed Abdula (Finance and Investment Program, School of Business and Management - Petra Christian University, 2022)
Trade is recognized as an important vehicle of economic growth, employment creation, income generation, and poverty reduction. As a result, trade occupies a prominent position in the development agenda of Ethiopia. The main objective of this study is to assess factors affecting firms of profitability in the case of Chiro town traders. From a total population, 93 sample respondents were identified using a simple random sampling technique. The findings from the study conducted revealed that most trader's businesses lack finance. Credit constraints operate in a variety of ways in Chiro town where undeveloped capital forces the trader to rely on self-financing or borrowing from friends or relatives. Lack of access to long-term credit forces traders in the town to rely on high-cost, short-term finance. Poor housing poses a major challenge to the business growth of traders in Chiro town. By encouraging the development of the construction sector oriented towards low-income groups, the government would address the housing problems affecting the business growth of traders. Finally, based on findings the researcher recommends Trader’s support program should have to be based on the identified critical factors. Major problems like lack of education, lack of working capital, and others that traders in the town face need to be addressed by prioritizing them following their severity as well as the availability of resources to run the operation. The loan repayment period for most traders was 1-2 years. The government should therefore establish friendly small loaning systems which would include low-interest rates to ensure continuity of these trader businesses.